EneoC, a queen-specific terpene synthase, produces the queen pheromone in epidermal secretory cells of Embiratermes neotenicus queens - Jitka Štáfková; Natan Horáček; Ondřej Lukšan; Romana Hadravová; Lenka Ulrychová; Jan Křivánek; Karel Harant; Ana Maria Costa-Leonardo; Robert Hanus (Insect Biochemistry and Molecular Biology, 2026)

How inquilinism shaped breeding systems in a termite host‐inquiline relationship - Johanne Timmermans; Simon Hellemans; Jan Křivánek; Esra Kaymak; Nicolas Fontaine; Thomas Bourguignon; Robert Hanus; Yves Roisin (Molecular Ecology, 2024)
Social insects have developed a broad diversity of nesting and foraging strategies. One of these, inquilinism, occurs when one species (the inquiline) inhabits the nest built and occupied by another species (the host). Obligatory inquilines must overcome strong constraints upon colony foundation and development, due to limited availability of host colonies. To reveal how inquilinism shapes reproductive strategies in a termite host‐inquiline dyad, we carried out a microsatellite marker study on Inquilinitermes inquilinus and its host Constrictotermes cavifrons . The proportion of simple, extended and mixed families was recorded in both species, as well as the presence of neotenics, parthenogenesis and multiple foundations. Most host colonies (95%) were simple families and all were monodomous. By contrast, the inquiline showed a higher proportion of extended (30%) and mixed (5%) families, and frequent neotenics (in 25% of the nests). This results from the simultaneous foundation in host nests of numerous incipient colonies, which, as they grow, may compete, fight, or merge. We also documented the use of parthenogenesis by female–female pairs. In conclusion, the classical monogamous colony pattern of the host species suggests uneventful development of simple foundations dispersed in the environment, in accordance with the wide distribution of their resources. By contrast, the multiple reproductive patterns displayed by the inquiline species reveal strong constraints on foundation sites: founders first concentrate into host nests, then must attempt to outcompete or absorb the neighbouring foundations to gain full control of the resources provided by the host nest.

The first evidence of microplastic occurrence in mine water: The largest black coal mining area in the Czech Republic - Kateřina Brožová; Jan Halfar; Kristina Čabanová; Oldřich Motyka; Silvie Drabinová; Pavel Hanus; Silvie Heviánková (Water Research, 2023)

Empirical insights on the use of sun-induced chlorophyll fluorescence to estimate short-term changes in crop transpiration under controlled water limitation - Kazi Rifat Ahmed; Eugenie Paul-Limoges; Uwe Rascher; Jan Hanus; Franco Miglietta; Roberto Colombo; Alessandro Peressotti; Andrea Genangeli; Alexander Damm (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Where should hydrology go? An early-career perspective on the next IAHS Scientific Decade: 2023–2032 - Theresa C. van Hateren; Harro J. Jongen; Hadeel Al-Zawaidah; Joris G.W. Beemster; Judith Boekee; Linda Bogerd; Sijia Gao; Christin Kannen; Ilja van Meerveld; Sjoukje I. de Lange; Felicia Linke; Rose B. Pinto; et al. (Hydrological Sciences Journal, 2023)

Sex-Pairing Pheromones in Three Sympatric Neotropical Termite Species (Termitidae: Syntermitinae) - Klára Dolejšová; Jan Křivánek; Blanka Kalinová; Romana Hadravová; Pavlína Kyjaková; Robert Hanus (Journal of Chemical Ecology, 2018)

Chemistry and Anatomy of the Frontal Gland in Soldiers of the Sand Termite Psammotermes hybostoma - Jana Krasulová; Robert Hanus; Kateřina Kutalová; Jan Šobotník; David Sillam-Dussès; Michal Tichý; Irena Valterová (Journal of Chemical Ecology, 2012)

Sex Pheromone and Trail Pheromone of the Sand Termite Psammotermes hybostoma - David Sillam-Dussès; Robert Hanus; Ashraf Oukasha Abd El-Latif; Pavel Jiroš; Jana Krasulová; Blanka Kalinová; Irena Valterová; Jan Šobotník (Journal of Chemical Ecology, 2011)

The frontal gland in workers of Neotropical soldierless termites - Jan Šobotník; David Sillam-Dussès; František Weyda; Alain Dejean; Yves Roisin; Robert Hanus; Thomas Bourguignon (The Science of Nature, 2010)

Agonistic Behavior of the Termite Prorhinotermes canalifrons (Isoptera: Rhinotermitidae) - Jan Šobotník; Robert Hanus; Yves Roisin (Journal of Insect Behavior, 2008)

(E,E)-α-Farnesene, an Alarm Pheromone of the Termite Prorhinotermes canalifrons - Jan Šobotník; Robert Hanus; Blanka Kalinová; Rafal Piskorski; Josef Cvačka; Thomas Bourguignon; Yves Roisin (Journal of Chemical Ecology, 2008)

Nitroalkenes and Sesquiterpene Hydrocarbons from the Frontal Gland of Three Prorhinotermes Termite Species - Rafal Piskorski; Robert Hanus; Soňa Vašíčková; Josef Cvačka; Jan Šobotník; Aleš Svatoš; Irena Valterová (Journal of Chemical Ecology, 2007)

Analysis of Insect Cuticular Hydrocarbons Using Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry - Josef Cvačka; Pavel Jiroš; Jan Šobotník; Robert Hanus; Aleš Svatoš (Journal of Chemical Ecology, 2006)